2016
DOI: 10.1016/j.polymdegradstab.2015.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Novolac phenolic resin and graphene aerogel organic-inorganic nanohybrids: High carbon yields by resin modification and its incorporation into aerogel network

Abstract: Graphene oxide (GO) modified with furfuryl alcohol and (3-aminopropyl) triethoxysilane (GOFASi) was used in two separate ways for preparation of novolac resin nanohybrids. In the first procedure, graphene-containing silica aerogel (GA) was obtained by incorporation of GOFASi into silica aerogel network using tetraethyl orthosilicate (TEOS). Then, GA was used as an additive in novolac resin matrix. In the second procedure, the synthesis of a hybrid novolac resin was accomplished by network formation via the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 84 publications
(117 reference statements)
0
27
0
Order By: Relevance
“…By the oxidation, modification, and hybrid network formation, the I D /I G value is increased which indicates that modification of CNTOH by HDBTMSPU and also sol-gel process have been carried out successfully [50]. The peaks at 532 and 1072 cm -1 are related to Si-O network [29,30]. Additionally, the peaks appeared at 731 and 941 cm -1 are related to Si-C group [58].…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…By the oxidation, modification, and hybrid network formation, the I D /I G value is increased which indicates that modification of CNTOH by HDBTMSPU and also sol-gel process have been carried out successfully [50]. The peaks at 532 and 1072 cm -1 are related to Si-O network [29,30]. Additionally, the peaks appeared at 731 and 941 cm -1 are related to Si-C group [58].…”
Section: Resultsmentioning
confidence: 94%
“…Accordingly, CNTX shows pore size in the range of 2-100 nm. However, the size of a large number of pores is 2-10 nm, which shows that CNTX can be categorized in mesoporous materials [29,30]. Considering cylindrical pore geometry, pore diameters can be calculated by D = 4V p /S BET , where D is the average pore diameter and V p is the pore volume.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These organic-inorganic hybrid materials can be prepared by co-condensation of modified polymers with metal alkoxides and formation of covalent bonding between the organic and inorganic components [16]. In sol-gel methods, hydrolysable alkoxysilanes are commonly used as coupling agents and pH, alkoxide type, water amount, temperature, and drying methods are important factors controlling the hydrolysis and condensation reactions [17][18][19][20]. Uniform distribution of silica/siloxane domains within a polymer matrix in co-condensation process may result in higher thermal and mechanical properties in such hybrid materials.…”
mentioning
confidence: 99%
“…They showed that 11.94% increase of char yield was achieved by incorporation of functionalized-CNT in silane-modified novolac resin matrix. A similar method was also used by this group for incorporation of (3-aminopropyl) triethoxysilane (APTES)-modified graphene and (3-glycidyloxypropyl)trimethoxysilane (GPTMS)-modified novolac resin into silica/ siloxane network [19]. They obtained high char value of 70.58% by incorporation of functionalized-graphene layers in silane-modified novolac resin matrix.…”
mentioning
confidence: 99%